Avaliação da prevalência de infecção pelo poliomavírus em transplantados renais e pancreáticos através da excreção urinária de células Decoy - Kroth, Leonardo Viliano (2007)
The present study evaluates aspects of polyomavirus infection in renal transplant patients. Recently, BK virus has been recognized as an important infectious agent because BK virus associated nephropathy (BKVN) has emerged as a significant cause of allograft failure. Currently, studies on its prevalence, risk factors, diagnostics and therapeutics methods, in different populations, are underway around the world. To date, this “newly emerged” infection remains mysterious in many aspects. The methods used to diagnosis polyomavirus infection are urinary cytology, urinary and plasmatic viral PCR and renal histology. Urinary cytology is an inexpensive and a simple method where urothelial cells with intranuclear viral inclusions are sought; these are called decoy cells and are thought to represent viral replication. The prevalence of decoy cells in renal transplants recipients is between 20 and 60%. Of these, 1 to 8% develops BKV nephropathy in witch case up to 80% may lose their grafts. No data on the prevalence of decoy cells in pancreas graft recipients has been published so far. In this study, we evaluated the prevalence of decoy cells in kidney, pancreas and kidney-pancreas recipients. The presence of decoy cells has been correlated with clinical variables, in an attempt to analyze risk factors. Two hundred and twenty one patients, 18 years-old or older, with more than 1 month follow up after transplantation, that attended the outpatients clinic between September and December 2006 were studied. The total prevalence of decoy cells was 16% (16.9% in kidney recipients, 5.9% in simultaneous kidney-pancreas recipients and 20% in pancreas alone recipients). There were no statistically significant differences between patients with either positive or negative urinary cytology for decoy cells, regarding demographic (gender, age, race) or clinical (time post-transplantation, donor type and history of delayed graft function or rejection, other associated viral infections and type of immunosuppressive drugs employed) variables.